Relationship between environmental knowledge, social influences, personal norms, media exposure and environmental awareness among students of Universiti Utara Malaysia - Mohd Nasri, Ashaari (2020)
The stability of the world ecosystem is increasingly threatened by irresponsible human activities that do not care about environmental issues. Therefore, the need for environmental awareness among public becomes paramount as an essential measure to restrain the situation before it becomes worse. The objective of this study is to identify factors affecting level of environmental awareness of UUM’s students. Specifically, this study examines the relationship between environmental knowledge, social influences, personal norms, media exposure and environmental awareness. Environmental awareness, as the dependent variable in this study, has been measured individually with all four independent variables without any existence of mediating factors. The data was collected through questionnaires among students of Universiti Utara Malaysia (UUM). A total of 248 returned questionnaires were analyzed using SPSS version 25. Pearson Correlation and Multiple Regression Analyses are used to identify relationship between IVs and DV. The results indicate that environmental knowledge, social influences, personal norms, and media exposure have positive and significant relationship towards environmental awareness of the UUM students. Finally, the theoretical and practical implications as well as limitations and recommendations for future research are also discussed in this thesis. Most importantly, students as the hope for future betterment of environment, must begin to develop themselves with such awareness in every sense of their daily life.